Design and implementation of a sensor-based wireless camera system for continuous monitoring in assistive environments - Li, Nan; Yan, Bo; Chen, Guanling; Govindaswamy, Prabhu; Wang, Jie (Personal and ubiquitous computing, 2010)
Camera-based surveillance system is an important tool for assistive environment to monitor those who may have physical or cognitive impairment. It is, however, expensive to deploy a wired surveillance system and difficult to continuously monitor a moving subject in a large facility where many cameras are deployed. In this paper, we first evaluate the performance of streaming camera images over wireless networks in both residential and office environments and present the quantitative results to show the feasibility of using wireless backbones for camera surveillance systems. We then propose sensor-integrated camera surveillance (SICS) to address the continuous monitoring problem. SICS uses wearable wireless sensors to locate moving subjects and automatically selects the camera covering the subject, allowing human operators to focus on only one screen to monitor an individual. SICS uses a self-organizing wireless mesh network to allow flexible deployment at reduced cost. An on-board image-processing algorithm is used to reduce the bandwidth consumption. Through empirical evaluation, we found that the automatic camera hand-off enabled by SICS was effective for continuous camera monitoring and a sophisticated wireless network management system is required to deploy the SICS in practice.